STABILIZED STATES AND METHODS OF CALCULATING ELECTRIC POWER LOSSES IN OPEN DISTRIBUTION POWER NETWORKS - Bozorov Islom Ro'ziyevich (American Journals Publishing, 2024)
This scientific article explores the concept of stabilized states and methodologies for calculating electricity losses in open distribution power networks. The stability of a power network is crucial for maintaining a reliable and efficient electricity supply. Understanding and accurately estimating losses are pivotal in designing resilient and cost-effective distribution systems. This article reviews existing approaches, introduces novel techniques, and discusses the implications for the optimization of open distribution power networks. Electricity distribution systems play a crucial role in ensuring a reliable and efficient supply of electrical energy to end-users. However, the open distribution power networks face challenges related to stability and energy losses. This scientific article explores stabilized states in open distribution power networks and various methods for calculating electricity losses. Understanding and mitigating these issues are essential for enhancing the overall performance and sustainability of power distribution systems.
Keywords: Open Distribution Power Networks, Stabilized States, Electricity Losses, Power System Stability, Energy Efficiency, Load Flow Analysis, Distribution Network Optimization, Voltage Stability, Power Quality, Renewable Energy Integration.